INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) AND ITS ROLE IN EDUCATIONAL ASSESSMENT - Marina Marina (Englisia: Journal of Language, Education, and Humanities, 2015)
This paper identifies the role of ICT in assessment practices in education. The significant factors that schools and teachers should consider include the benefits it can provide to improve and enhance assessment. The primary focus of this paper is: What are the roles ICT can provide to support assessment in education? ICT has several roles and supports in educational assessment practices. This paper empha-sizes its roles in two parts: testing, and tasks. ICT can be used in testing to administer tests, to score the tests, to analyse the result and to facilitate teachers in assessing learning outcomes. Besides, ICT can be integrated in completing student’s task such as portfolio and project-based assessment. ICT provides opportunities for students to create electronic versions of their portfolio. ICT can also support students to complete their project. It is essential for teachers to realise that the rubric used to assess e-portfolios and projects must also assess students’ technology use.